Principal component analysis of salivary cytokines and hormones in the acute stress response - Ryznar, Rebecca; Wong, Cheyenne; Onat, Erin; Towne, Francina; LaPorta, Anthony; Payton, Mark (Frontiers in Psychiatry, 2022)
The acute stress response is characterized by activation of multiple interconnected systems in the body, resulting in the release of a flood of hormones and immune mediators into circulation. In addition to detection of these molecules in the serum, saliva can serve as a source of these markers as well and can be collected in a non-invasive way. The complete profile of salivary biomarkers associated with the hypothalamic pituitary adrenal/gonadal axes and the immune system during the acute stress response has not been fully elucidated. In a cohort of 62 first responders engaged in a stress training exercise, we set out to determine patterns of cytokine, chemokine and hormone shifts during the acute stress response. Salivary samples were collected immediately before (pre-stress), immediately after (post-stress) and one hour after the stress test (recovery). Multiplex ELISA panels of 42 cytokines and 6 steroid and thyroid hormones were used to determine concentrations of these biomarkers during the three aforementioned time points. Principal component analysis was conducted to determine patterns in the large data sets collected. In our ≥0.3 loading factor analysis, for pre-stress versus post, post-stress versus recovery and pre-stress versus recovery, a total of three, four and three factors accounted for 56.6%, 68.34% and 61.70% of the biomarker variation for each phase respectively. In the ≥0.7 loading principal component analysis, three, four and three factors were found for pre-stress versus post, post-stress versus recovery and pre-stress versus recovery stages, respectively. Of note, in our ≥0.3 loading principal component analysis, MCP1 was present in all three factors from pre-stress to post-stress, and fractalkine was found to be in all four factors post-stress versus recovery and pre versus recovery from stress. Additionally, hormones testosterone, estradiol, T4 and T3 grouped together consistently in the same factor for all phases of acute stress in both ≥0.3 and ≥0.7 factor loading analysis. Overall, our results identified specific patterns of immune markers and hormones that shift during acute stress and warrant further investigation to understand their mechanistic role in regulating the stress response.